Adrenergic blockers and the risk for common solid cancers: a case-control study - Numbere, Beade; Fleming, Kate M.; Walker, Alex; Card, Timothy R. (Lippincott, Williams & Wilkins, 2017)
Laboratory studies have suggested that adrenergic blockers may inhibit the proliferation and migration of cancer cells, but epidemiological evidence of their effect on cancer incidence has proven inconsistent. We therefore conducted a case-control study using the Clinical Practice Research Datalink to assess the effect of adrenergic blockers on the incidence of prostate, lung, bowel and breast cancers. From among patients aged 18 years or older who contributed at least 2 years of prospectively gathered data between 1 January 1987 and 31 December 2012, we selected incident cases of relevant cancers and controls, frequency matched 10 : 1 by age. Logistic regression was used to adjust effect estimates for age, sex, smoking, alcohol use, and a number of potentially confounding comorbidities and coprescriptions. A total of 18 968 colorectal, 19 082 lung, 21 608 prostate and 29 109 breast cancers were identified. We found no evidence of a protective effect of adrenergic blockade in lung and prostate cancers and found a slightly increased risk for colorectal and breast cancers in users. This was largely explained by the effects of confounding in multivariate analyses, with final odds ratio estimates for lung, colorectal, breast and prostate cancers of 0.99 [95% confidence interval (0.96-1.04)], 1.14 (1.09-1.18), 1.10 (1.06-1.14), and 1.01 (0.98-1.05), respectively, for beta-blocker exposure, and final odds ratio estimates for lung, colorectal and breast cancer of 1.03 (0.97-1.09), 1.13 (1.07-1.20), and 1.08 (1.00-1.17), respectively, for alpha-blocker exposure. We found no evidence to suggest that adrenergic blocker use prevents common cancers. Indeed, we found a slightly increased risk for colorectal and breast cancers, which may reflect